2022
DOI: 10.3390/agronomy12081974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Living Grass Mulch on Soil Properties and Assessment of Soil Quality in Chinese Apple Orchards: A Meta-Analysis

Abstract: Soil degradation has exacerbated the gap between crop yield and increasing food demands, and unreasonable field management is one of the main reasons for soil degradation. As a classic orchard soil management mode, living grass mulch can effectively change the hydrothermal environment and soil physicochemical properties of the ‘soil–vegetation–atmosphere’ microclimate of apple orchards. However, these improvement effects are mainly affected by climatic conditions, mulch methods, vegetation varieties and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Of note, the HV treatment had a more significant impact on nitrogen-related indicators (TN, AN, DTN, NO 3 − -N, NH 4 + -N). Similarly, Tang et al [ 43 ] reported that white clover mulch significantly increased the soil TN content in apple orchards, while ryegrass had no significant effect. This phenomenon is attributed to the fact that both hairy vetch and white clover are leguminous crops and have strong nitrogen fixation capabilities [ 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…Of note, the HV treatment had a more significant impact on nitrogen-related indicators (TN, AN, DTN, NO 3 − -N, NH 4 + -N). Similarly, Tang et al [ 43 ] reported that white clover mulch significantly increased the soil TN content in apple orchards, while ryegrass had no significant effect. This phenomenon is attributed to the fact that both hairy vetch and white clover are leguminous crops and have strong nitrogen fixation capabilities [ 44 ].…”
Section: Discussionmentioning
confidence: 95%
“…(4) Grass cultivation in orchards has the function of adjusting the soil temperature. The large-scale changes in the external ambient temperature can be blocked by the grass, thereby reducing the temperature fluctuation of the soil surface, which is conducive to the growth of fruit tree roots (Hao et al, 2021;Tang et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soil-enzyme activity responded to mulching treatments, and CAT, sucrose, and cellulase were more sensitive to mulching treatments than to other soil properties [35]. Beta-glucosidase activity is one of the most sensitive and reliable indices for assessing soil quality [36].…”
Section: Discussionmentioning
confidence: 99%